Pengaruh status gizi ibu menyusui terhadap eksklusivitas pemberian ASI dan pertumbuhan bayi di RSUD Prof. Dr. WZ. Johannes Kupang - Beatrix Soi; Madarina Julia; R Dwi Budiningsari (Minat S2 Gizi dan Kesehatan, Prodi S2 IKM, FK-KMK UGM, 2006)
Background : Numerous research have been made to find out contributive factors of the exclusive breastfeeding.Objective: The objective of this study was to find out whether mothers’ nutritional status had any influence on the exclusivity of breastfeeding and on the growth of their babies up to 4 months.Methods: This observational study was carried out with a prospective cohort design and lasted from November 2004 to May 2005. The subjects were 80 pairs of mother and baby treated at the Obstetric and Gynecology Unit (UPF) of Local Public Hospital (RSUD) Prof. Dr. W.Z. Johannes at Kupang – NTT. The subjects were divided into two groups namely Undernutrition status group marked by <23,5 cm mid arm-circumference, and control group comprised 46 mothers of well- nutrition status who had bigger mid arm-circumference >23,5 cm. Observed babies were those of normal or spontaneous delivery, non twin with >2500 g birth weight. Follow up observations were made at family home and the data on breastfeeding characteristics were collected by interview, babies weight were measured by Secca baby scale with 0,01 kg level of accuracy mid arm-circumference was measured by means of LILA tape, and body length was measured using length-board. Tools measure with 0,1 cm level of accuracy. Some statistical tests were used namely Chi-Square; student’s t-test; and while Kaplan Meier log-rank test as needed.Results: More than 50% of under-nutrition mothers were under 25 years old. Chi-Square test shows that significant difference between mother’s age was (p=0,04). More than 50% of the KEK group gave birth for the first time or ‘primipara’ (p=0,25). Kaplan Meier analysis showed that there was no difference between survival median of breastfeeding be- tween the both group (p=0,53). t-test showed that there were significant differences of the babies body weight of the both KEK and non KEK mothers, namely pd”0,01, p=0.01, and p=0.03 in the first, second, third, and the fourth month respectively. In terms of the average babies body length, the t-test also showed significant differences between both groups with p=0.02 and p=0.01 in the third and the fourth month respectively.Conclusion: I can be concluded that mother’ nutrition status did not have any influence on the exclusivity of breastfeeding, however, it did significantly influence babies growth from 0- 4 month.